Comparison of intracoronal bleaching methods on teeth discolored by different antibiotic pastes - TARÇIN, BİLGE; İRİBOZ, EMRE; SAZAK ÖVEÇOĞLU, HESNA (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2017)
Aim: To compare the bleaching efficacy of sodium perborate with different activation methods on crowns discolored by two different antibiotic pastes. Materials and Methods: Eighty-five extracted human incisors were prepared to size #30 using ProTaper rotary instruments. After chemomechanical preparation and irrigation procedures, the specimens received triple antibiotic paste (TAP, n = 40), minocycline paste (MP, n = 40), or calcium hydroxide (n = 5, control group) and coronally sealed with temporary filling material. Spectrophotometric readings were obtained on day 0uweek 4. Data were analyzed with the MannuWhitney U-test and Wilcoxon sign test (P < 0.05). Sodium perborate was then inserted into the pulp chambers of discolored teeth (four subgroups, n = 10) and activated by heat or ultrasonically using two different frequencies and times. Spectrophotometric readings were obtained on days 3u7. Data were analyzed by the MannuWhitney U-test and KruskaluWallis test (P > 0.05). Results: Both groups showed statistically significant coronal discoloration at each time interval (P < 0.01), but their final shades did not significantly differ between the groups (P > 0.05). Although the MP subgroups exhibited more bleaching than the TAP subgroups on days 3 and 7, the difference was not significant (P > 0.05). The bleaching results for the sodium perborate activation techniques did not significantly differ among groups (P > 0.05). Conclusions: Both antibiotic pastes induced crown discoloration that was reversible using all sodium perborate bleaching techniques.
Keywords: Bleaching; minocycline; sodium perborate; spectrophotometric analysis; triple antibiotic paste; SODIUM PERBORATE; CALCIUM HYDROXIDE; APICAL PERIODONTITIS; TOOTH DISCOLORATION; MEDICAMENTS; EFFICACY; METRONIDAZOLE; CIPROFLOXACIN; REGENERATION; PEROXIDE